2019
DOI: 10.3126/jonmc.v8i2.26716
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Extracranial Carotid Arteries in Ischemic Stroke Patients Using Color Doppler Sonography and Correlation with Various Risk Factors

Abstract: Background: Cerebral ischemic stroke is the major cause of death after ischemic heart disease and malignancies, among which major cases of stroke results from atherosclerosis of intra and extra-cranial carotid vessels. The aim of this study is to evaluate the extracranial carotid arteries in patients with ischemic stroke and correlation with various risk factors. Materials and Methods: A cross sectional study of the patients with ischemic stroke presented in Radiology department of Nobel Medical College … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…This finding differs from previous evidence in which the extracranial carotid artery was the most common plaque location. 4,11 This is probably due to ethnic differences, where atherosclerotic lesions in Asian people are more frequently found in the intracranial vessels. 12 The causes are still unknown but presumably related to genetics and nutritional factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding differs from previous evidence in which the extracranial carotid artery was the most common plaque location. 4,11 This is probably due to ethnic differences, where atherosclerotic lesions in Asian people are more frequently found in the intracranial vessels. 12 The causes are still unknown but presumably related to genetics and nutritional factors.…”
Section: Discussionmentioning
confidence: 99%
“…This study has similar findings to a study in India which showed that more plaque is located in the common carotid artery. 11 Vulnerable plaque, indicated as plaque with a high degree of echolucency, is prone to rupture and may result in thrombus formation. In this study, the most common plaque found was type III, followed by type II, indicating that the plaque found was more stable.…”
Section: Discussionmentioning
confidence: 99%